The legacy of Finnish-Estonian air ion and aerosol workshops - Kulmala, Markku; Horrak, Urmas; Manninen, Hanna E.; Mirme, Sander; Noppel, Madis; Lehtipalo, Katrianne; Junninen, Heikki; Vehkamäki, Hanna; Kerminen, Veli-Matti; Noe, Steffen M.; Tammet, Hannes (Finnish Environment Institute, 2016)
Atmospheric air ions, clusters and aerosol particles participate in a variety of atmospheric processes and considerably affect e.g. global climate and human health. When measured, air ions as well as atmospheric clusters and particles have been observed to be present practically always and everywhere. In this overview, we present a brief summary of the main achievements and legacy of the series of workshops organized mainly by the University of Helsinki and the University of Tartu. The legacy covers the development and standardization of new instruments, such as ion spectrometers, mass spectrometers and aerosol particle counters, as well as work toward theoretical understanding of new-particle formation and evolution of atmospheric clusters. One important legacy is the establishment of the SMEAR-Estonia station at Jarvselja. Peer reviewed